Comparison of various Helicobacter pylori diagnostic techniques in samples isolated from Iraqi patients - Al-Hussain Alkawaz, Ali Jabbar Abd; Sabah Naser, Maryam; Obaid, Ali Jalil (Pharmakeftiki, 2025)
The Helicobacter pylori infection is a major global health concern, contributing to various gastrointestinal disorders, including gastritis, peptic ulcers, and gastric cancer. Disease management relies on the availability of both accurate and reliable diagnostic methods. This study evaluates and compares the diagnostic accuracy of three widely used non-invasive tests (the 13C-urea breath test or 13C-UBT, the stool antigen test, and serological testing) against endoscopy (as the gold standard) in Jood Specialist Lab in Hillah (Iraq) between February and December 2024. A total of 100 patients was included in this study, and specimens were inspected using each of the aforementioned tests. Results showed that the 13C-UBT had the highest sensitivity (98.9%) and specificity (76.9%), which makes it the best non-invasive test for the diagnosis of an H. pylori infection. Meanwhile, the stool antigen test exhibited a slight lower performance in both sensitivity (94.8%) and specificity (65.2%), while the serological testing exhibited the lowest specificity (24.5%), resulting in a greater frequency of false positives. These findings underscore the limitations of serological testing and reinforce 13C-UBT’s position as the method of choice for the non-invasive diagnosis of H. pylori infections in Iraqi patients.